ANALISIS PERANGKAT PEMBELAJARAN GURU PENDIDIKAN AGAMA ISLAM BERDASARKAN KURIKULUM 2013 DI SMP NEGERI 1 PERCUT SEI TUAN DELI SERDANG - Nur Aini (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
The purpose of this study was to determine: (1) Suitability of 2013Curriculum Annual Program Preparation, (2) Suitability of Compilation ofthe 2013 Curriculum Semester Program. (3) Appropriate components ofthe Learning Implementation Plan (RPP) based on Permendikbud No.222016. The approach used in this study is a qualitative approach The dataanalysis technique used is data collection, data reduction and data presentation conclusions. The technique of guaranteeing the validity of the data is done by checking trust, checking examination and checkingdependency. The results of the study can be concluded that the results ofthe Analysis of Suitability of Annual Programming, Semester Program,and Learning Implementation Plan can be categorized as "In Accordance"because the results are obtained based on the scores of the AnnualProgram, Semester Program and Learning Implementation Plan (RPP)compiled by the teacher Islamic religious education in SMP Negeri 1Percut Sei Tuan Deli Serdang.